FRI0269 COMPARATIVE STUDY OF INFLIXIMAB VERSUS ADALIMUMAB IN REFRACTORY UVEITIS DUE TO BEHÇET'S DISEASE. NATIONAL MULTICENTER STUDY OF 177 CASES. (June 2019) - Atienza-Mateo, Belén; Martín-Varillas, José Luis; Calvo-Río, Vanesa; Demetrio-Pablo, Rosalía; Beltrán, Emma; Sánchez-Bursón, Juan; Mesquida, Marina; Adan, Alfredo; Hernandez, Victoria; Hernández-Garfella, Marisa; Valls-Pascual, Elia; Martinez-Costa, Lucía; et al.
Abstract : Background: Uveitis is one of the major causes of disability of Behçet's disease (BD). According to the "Expert panel recommendations", anti-TNF therapy with infliximab (IFX) or adalimumab (ADA) may be considered as first- or second-line therapy for patients with BD-ophthalmic manifestations. Objectives: To compare IFX versus ADA as first biologic drug in refractory uveitis due to BD for 1-year period. Methods: Multicenter study of BD-associated uveitis refractory to conventional non-biologic treatment. Dosing schedule: IFX 3-5 mg/kg iv at 0, 2 and 6 weeks and then every 4-8 week, and ADA 40 mg/sc/every other week without loading dose. Main comparative outcome measures: safety and efficacy, assessing the intraocular inflammation, macular thickness, visual acuity, degree of immunosuppression load, drug retention, and glucocorticoid-sparing effect. Results: 177 patients (316 affected eyes) were included. IFX was used in 103 and ADA in 74. No significant differences at baseline were observed regarding main demographic features, previous therapy and ocular severity. After 1 year of therapy, we observed an improvement in all ocular parameters in IFX vs ADA groups: AC inflammation (78.18% vs 92.31%), vitritis (78.95% vs 93.33%), retinal vasculitis (97% vs 95%), macular thickness (264.89±59.74 vs 250.62±36.85), and BCVA (0.67±0.34 vs 0.81±0.26). Drug withdrawal was observed in 57 (55.33%) of IFX group and in 21 (28.37%) of ADA group. Conclusion: After 1 year of therapy in refractory BD-associated uveitis, ADA showed a statistically better outcome than IFX in improvement of BCVA, vitritis and drug retention. References: [1] Levy-Clarke G, et al. Expert panel recommendations for the use of anti-tumor necrosis factor biologic agents in patients with ocular inflammatory disorders. Ophthalmology. 2014; 121:785-96. [2] Santos-Gómez M, et al. The effect of biologic therapy different from infliximab or adalimumab in patients with refractory uveitis due to Behçet's disease: results of a multicentre open-label study. Clin Exp Rheumatol 2016; 34 (6 Suppl 102): S34-40 [3] Atienza-Mateo B, et al. Anti-IL6-Receptor Tocilizumab in Refractory Uveitis Associated With Behçet's Disease. Multicenter Retrospective Study. Rheumatology (Oxford). 2018 May 1;57(5): 856-864. [4] Martín-Varillas JL, et al. Successful Optimization of Adalimumab Therapy in Refractory Uveitis Due to Behçet's Disease. Ophthalmology. 2018 Mar 27. Disclosure of Interests: Belén Atienza-Mateo: None declared, José Luis Martín-Varillas: None declared, Vanesa Calvo-Río: None declared, Rosalía Demetrio-Pablo: None declared, Emma Beltrán: None declared, Juan Sánchez-Bursón: None declared, Marina Mesquida: None declared, Alfredo Adan : None declared, Victoria Hernandez: None declared, Marisa Hernández-Garfella: None declared, Elia Valls-Pascual: None declared, Lucía Martinez-Costa: None declared, Agusti Sellas-Fernández: None declared, Miguel Cordero-Coma: None declared, Manuel Díaz-Llopis: None declared, Roberto Gallego: None declared, José L. García-Serrano: None declared, Norberto Ortego: None declared, Jose M. Herreras: None declared, Alejandro Fonollosa: None declared, Ángel García-Aparicio: None declared, Olga Maiz-Alonso Speakers bureau: Pfizer, Ana Blanco: None declared, Ignacio Torre-Salaberri: None declared, Cruz Fernandez-Espartero: None declared, Vega Jovani: None declared, Diana Peiteado: None declared, Esperanza Pato: None declared, Juan Cruz: None declared, Carlos Férnandez-Cid: None declared, Elena Aurrecoechea: None declared, Miriam García-Arias: None declared, Santos Castañeda Consultant for: Amgen, BMS, Pfizer, Lilly, MSD, Roche, Sanofi, UCB, Miguel A. Caracuel-Ruiz: None declared, Carlos A. Montilla-Morales: None declared, Antonio Atanes-Sandoval: None declared, Félix Francisco: None declared, Santos Insua: None declared, Senen González-Suárez: None declared, Amalia Sanchez-Andrade: None declared, Fernando Gamero: None declared, Luis F. Linares Ferrando: None declared, Fredeswinda Romero: None declared, A. Javier García-González: None declared, RAQUEL ALMODOVAR: None declared, Enrique Minguez: None declared, Carmen Carrasco-Cubero: None declared, Alejandro Olive: None declared, Julio Vázquez: None declared, Oscar Ruiz-Moreno: None declared, Fernando Jiménez-Zorzo: None declared, Javier Manero: None declared, Santiago Muñoz Fernandez: None declared, Cristina Fernández-Carballido: None declared, Esteban Rubio-Romero: None declared, Fred Antón Pages: None declared, Francisco J. Toyos Sáenz de Miera: None declared, Myriam Gandia Martinez: None declared, David Díaz Valle: None declared, Francisco J López-Longo: None declared, Joan Miquel Nolla: None declared, Enrique Raya: None declared, Marcelino Revenga: None declared, J. Luis Hernández: None declared, Monica Calderón-Goercke: None declared, D. Prieto-Peña: None declared, Iñigo González-Mazón: None declared, Lara Sánchez Bilbao: None declared, Miguel Á. González-Gay: None declared, Ricardo Blanco: None declared